Effect of sintering parameters on physical properties of SS 316L alloy compact - Mohd Faizul Farhan, Ahmad Hamidi; W. S., Wan Harun; Osada, Toshiya; S. A., Che Ghani; Dayangku Noorfazidah, Awang Shri (Penerbit UiTM, 2017)
Recently, metal injection moulding (MIM) has been identified as an economical fabrication technique for metal components. MIM, adapted from plastic injection moulding, has four major processing stages, which are: mixing of powder and binder system to produce feedstock, injection moulding, debinding and sintering. In this paper, the physical properties of SS 316L alloy sintered compact sintered at three different sintering parameters were discussed. Thermal properties of the feedstock were characterized by Thermogravimetric Analyzer (TGA) analysis. The debound compacts were sintered at 1100, 1200, and 1300 °C for 3 hours in the high pure argon atmosphere. The heating rate has been set at 10°C/min. The relative density, dimensional shrinkage and microstructure of the sintered compact were investigated. The relative density and dimensional shrinkage increased with the sintering parameters due to high densification of the sintered compact. Some pore sizes seemed to decrease with the increase in sintering temperature. Different sintering temperature shows a significant effect on the physical properties of the sintered compact.